Nucleation and growth process of atomic layer deposition platinum nanoparticles on strontium titanate nanocuboids. (11th April 2017) - Wang, Chuandao; Hu, Linhua; Poeppelmeier, Kenneth; Stair, Peter C; Marks, Laurence
Abstract: Uniform, well-dispersed platinum nanoparticles were grown on SrTiO3 nanocuboids via atomic layer deposition (ALD) using (methylcyclopentadienyl)trimethylplatinum (MeCpPt(Me)3 ) and water. For the first half-cycle of the deposition particles formed through two sequential processes: initial nucleation and growth. The final particle size after a single complete ALD cycle was dependent on the reaction temperature which alters the net Pt deposition per cycle. Additional cycles resulted in further growth of previously formed particles. However, the increase in size per cycle during additional ALD cycles, beyond the first, was significantly lower as less Pt was deposited due to carbonaceous material that partially covers the surface and prevents further MeCpPt(Me)3 adsorption and reaction. The increase in particle size was also temperature dependent due to changes in the net Pt deposition. Pt nanoparticles increased in size by 59% and 76% after 15 ALD cycles for reaction temperatures of 200 °C and 300 °C, respectively. There was minimal change in the number of particles per unit area as a function of reaction time, indicating that there was minimal Ostwald ripening or secondary nucleation for the reaction conditions.